1995
DOI: 10.1016/0043-1648(94)06544-6
|View full text |Cite
|
Sign up to set email alerts
|

Friction and wear behaviour of ceramic-hardened steel couples under reciprocating sliding motion

Abstract: The friction and wear behaviour of ZrO*-Y203, Zr02-Y203--Ce02 and ZrQ--A1203 composite ceramics against hardened steel AISI-52100 were investigated using a pin on plate configuration under reciprocating motion. The reproducibility of the results was examined in this configuration. Wear characteristics were separated into system and material contributions. Under the conditions used, all the ceramic components exhibited rather low wear rates (less than 10m6 mm3 N-' m-'). The frictional behaviour of ceramic-metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Also it can be observed that, after 2000 m, the a-and b-sialon ceramics presents the lower and the highest friction coefficient, respectively, under dry testing conditions. According to literature [20][21][22], the lowest friction behaviour was expected for a-sialon, as observed, since the a-phase exhibits higher hardness and thermal shock resistance compared to b-phase.…”
Section: Resultssupporting
confidence: 52%
“…Also it can be observed that, after 2000 m, the a-and b-sialon ceramics presents the lower and the highest friction coefficient, respectively, under dry testing conditions. According to literature [20][21][22], the lowest friction behaviour was expected for a-sialon, as observed, since the a-phase exhibits higher hardness and thermal shock resistance compared to b-phase.…”
Section: Resultssupporting
confidence: 52%
“…The stiffness of materials, or the ratio of hardness to Young's modulus, H / E , has also been proposed as one of the key parameters controlling wear . Usually, a higher value of H / E means improved resistance to scratching in the contact area during dry sliding . Figures (e)–(f) plot the H / E value as a function of ZrO 2 content with its effects on COF and wear rate.…”
Section: Discussionmentioning
confidence: 99%
“…32 A higher value of H/E means that the materials have improved resistance to scratching in the contact area during dry sliding. 33,34 The results in the previous section show that hardness increases with the increment of Ti 5 Si 3 content, and the Young's modulus of Ti 5 Si 3 (E = 156 GPa) is lower than that of Ti 3 Si(Al)C 2 , so wear resistance can be improved.…”
Section: Wear Behaviormentioning
confidence: 87%